Drive : vehicle sketches and renderings - Robertson, Scott, 1966-; Gardner, Daniel, ....-; Naeem, Annis, ....- (Culver City : Designstudio, 2010)
Robertson's latest vehicle designs intended for the video game space, featuring skillfully drawn sketches and renderings. Divided into 4 chapters, each with a different aesthetic: aerospace, military, pro sports and salvage, the book is bursting with black-and-white and full-colour images of sports cars, big rigs and off-road vehicles.